Political considerations and fiscal regulation in a spatial duopoly: Effects on product differentiation - Hamid Hamoudi; Ana Belen Miquel Burgos; Ourania Dimakou (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
We examine the impact of political orientation on fiscal regulation and product differentiation within a spatial duopoly. Using a modelling approach a la Hotelling, we explore how the regulator’s political stance -whether pro-consumer or pro-business- affects market outcomes through distinct optimal designs of fiscal intervention. We identify three regulatory profiles: (i) pro-consumer regulation with high tax rates leading to minimal product differentiation and lower prices; (ii) pro-business regulation with no taxation resulting in maximum product differentiation and higher prices, and (iii) moderate regulation, balancing the interests of firms and consumers, in which taxes can be moderate but the firms are not induced to follow the regulator’s designated levels of differentiation. Our findings highlight the significant role of political orientation in shaping market dynamics and regulatory effectiveness, emphasising the need to consider political factors and the balancing of various actors in policy design within spatial competition models.